• Oct 22nd 2010, 07:24 AM
andyboy179
hi, i need to make this into a quadrattic equation but there is a pert on the table which i can't remember what to do!

when you have x then -3,-2,-1,0,1,2,3
under that you puy Y and i can remember how to work that out! if you can help i will be very thankful!

my question is Y= x^2-4x+1 by the way
• Oct 22nd 2010, 07:46 AM
Unknown008
Replace the values of x in the equation given to you!

For example, under -3, you put:

$\displaystyle (-3)^2 - 4(-3) + 1 = 9 + 12 + 1 = 22$

Hence:

$\displaystyle \begin{array}{|c|c|c|c|c|c|c|c|}\hline x & -3 & -2 & -1&0&1&2&3 \\ \hline y & 22 &&&&&&\\ \hline \end{array}$
• Oct 22nd 2010, 08:45 AM
andyboy179
thanks for answering my question! under -2 it would be 11?
• Oct 22nd 2010, 08:47 AM
Unknown008
$\displaystyle (-2)^2 - 4(-2) + 1 = 4 + 8 + 1$

Does this equal 11?
• Oct 22nd 2010, 08:50 AM
andyboy179
no its 13, i think i got it now!! would -1=3?
• Oct 22nd 2010, 08:52 AM
pickslides
Quote:

Originally Posted by andyboy179
would -1=3?

I get 6
• Oct 22nd 2010, 08:54 AM
Unknown008
Think of it again:

$\displaystyle (-1)^2 - 4(-1) + 1 = 1 + 4 + 1$

Does this make 1?

remember that when you multiply two negative numbers, they become a positive number.
• Oct 22nd 2010, 08:59 AM
andyboy179
would 0 =1
1=0
2=1
3=1???
• Oct 22nd 2010, 09:03 AM
Unknown008
for 0: yes.

For 1: $\displaystyle (1)^2 - 4(1) + 1 = 1 - 4 + 1$

For 2: $\displaystyle (2)^2 - 4(2) + 1 = 4 - 8 + 1$

For 3: $\displaystyle (3)^2 - 4(3) + 1 = 9 - 12 + 1$

Hm.. you need to work your basic calculations more...
• Oct 22nd 2010, 09:03 AM
andyboy179
actually would this be it:
-3=19
-2=11
-1=5
0=1
1=-1
2=-1
3=1
• Oct 22nd 2010, 09:06 AM
Unknown008
Are you sure you posted the right equation?
• Oct 22nd 2010, 09:07 AM
andyboy179
cr@p, no i didn't its -4X sorry!!!!!!!!
• Oct 22nd 2010, 09:14 AM
Unknown008
I still have no idea what the equation actually is... (Speechless)